2013
DOI: 10.1620/tjem.231.293
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of GAP-43 Protein in the Rostral Brain Neurons of Early Chick Embryos

Abstract: Brain development is composed of several processes, which are chronologically and mechanistically overlapping each other. However, the process of the earliest neural circuit formation in the rostral brain is less understood compared with other processes in brain development, in part because of the lack of appropriate molecular markers. Accordingly, the identification of molecular markers for nerve cells may accelerate the detailed analysis of neural development. Growth associated protein 43 (GAP-43) is a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…There is evidence that excessive ROS can induce mitochondrial function damage and reduce the production of ATP in paclitaxel-treated animals at both the early and late time points 13. Another point here is that paclitaxel leads to significant deficits in complex I-mediated and complex II-mediated respiration in sensory axons 26. The results of the present study reported that paclitaxel-induced neuropathic pain was associated with mitochondrial damages.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…There is evidence that excessive ROS can induce mitochondrial function damage and reduce the production of ATP in paclitaxel-treated animals at both the early and late time points 13. Another point here is that paclitaxel leads to significant deficits in complex I-mediated and complex II-mediated respiration in sensory axons 26. The results of the present study reported that paclitaxel-induced neuropathic pain was associated with mitochondrial damages.…”
Section: Discussionsupporting
confidence: 56%
“…Peripheral neuropathy caused by chronic, distal, and symmetrical chemotherapy, commonly accompanied by a neuropathic pain syndrome, is a serious dose-limiting complication associated with several first-line chemotherapeutic agents 26. Paclitaxel (Taxol ® ) has long been established as a preferred chemotherapeutic agent for the treatment of solid tumors in clinical practices 10,14.…”
Section: Introductionmentioning
confidence: 99%
“…In damaged facial and sciatic nerves, regeneration is associated with an increase in growth-associated protein 43 mRNA levels in both spinal motor neurons and dorsal root ganglion neurons[40]. It has been suggested that growth-associated protein 43 probably plays a key role in FK-506-induced neuroregeneration, since this drug massively increases the phosphorylation of this major neuronal phosphoprotein implicated in neuronal growth[4142].…”
Section: Discussionmentioning
confidence: 99%
“…58 In the cerebellum, GAP-43 mRNA expression appears to be critical in granule cell differentiation/migration and in parallel and climbing fiber axonal outgrowth and synaptogenesis. 59 During development, cerebellar GAP-43 mRNA expression increases from birth to postnatal day (PND)7, then gradually declines during maturation.…”
Section: Relationship To Developmentmentioning
confidence: 99%